A systematic review of complementary feeding practices in South Asian infants and young children: the Bangladesh perspective - Logan Manikam; Alexandra Robinson; Jia Ying Kuah; Hrisheekesh J. Vaidya; Emma C. Alexander; George W. Miller; Kunjshri K. Singh; Victoria Dawe; Sonia Ahmed; Raghu Lingam; Monica Lakhanpaul (BMC Nutrition, 2017)
Abstract Background Sub-optimal nutrition among children remains a problem across South Asia (SA). Appropriate complementary feeding practices (CFP) can greatly reduce this risk. The primary objective of this systematic review (SR) of CF studies was to assess timing, dietary diversity, meal frequency and influencing factors in children under two in Bangladesh. Methods Searches included English-language research published between January 2000 and June 2016 within MEDLINE, EMBASE, Global Health, Web of Science, OVID Maternity & Infant Care, BanglaJOL, Cochrane Library, CINAHL, POPLINE and WHO Global Health Library. Eligibility criteria: primary research concerning the adequacy of complementary feeding practices in South Asian children aged 0–2 years and/or their families. We excluded interventional papers and those focusing exclusively on breast-feeding. In total 45,712 titles and abstracts were screened against inclusion criteria, 860 of which received independent full text review by two reviewers. 36 papers relevant to Bangladesh were identified. The ‘EPPI-Centre Weight of Evidence Framework’ was used to objectively assess each study’s value in answering the review question. As per WHO Infant and Young Children Feeding Guidelines (IYCF), introduction of CF was assessed as the proportion of infants aged 6–8 months who received solid, semi-solid or soft foods. Search terms were: “children”, “feeding” and “Asians” with their derivatives. Two researchers undertook study selection, data extraction and quality appraisal. Results Three cohort, 30 cross-sectional and 3 mixed methods studies were included. Despite adopting the WHO IYCF Guidelines, sub-optimal CF practices were found in many studies. Timely initiation of CF practices ranged from 24 to 83%. Achieved minimum dietary diversity ranged from 25% to 44% and minimum meal frequency from 33% to 81%. Influencing factors included maternal education, poor knowledge of CF practices and socioeconomic variables. Conclusions This is the first systematic review to evaluate CF practices in Bangladesh. Despite adoption of the WHO IYCF guidelines, inadequate CFP remain in communities across Bangladesh. Trial registration PROSPERO Registration No: CRD42014014025 .